2022
DOI: 10.3390/pathogens11020184
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cellular Metabolism during Candida-Host Interactions

Abstract: Microscopic fungi are widely present in the environment and, more importantly, are also an essential part of the human healthy mycobiota. However, many species can become pathogenic under certain circumstances, with Candida spp. being the most clinically relevant fungi. In recent years, the importance of metabolism and nutrient availability for fungi-host interactions have been highlighted. Upon activation, immune and other host cells reshape their metabolism to fulfil the energy-demanding process of generatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 131 publications
(170 reference statements)
0
15
0
Order By: Relevance
“…Fungal Cell Metabolism. Adapting to the novel environment related to the initiation or further dissemination of infection requires Candida fungi to respond immediately and effectively to the stress associated with the colonization of a new infectious niche, consisting of fluctuations in the availability of nutrients, limits in access to essential microelements, physicochemical changes in the surroundings, the influence of other microorganisms, and activity of host defense cells [148,149]. One of the most important factors that influences Candida cell metabolism during infection is the availability and type of carbon source, where glucose is preferred.…”
Section: Environmental Stress Response and Related Changes Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal Cell Metabolism. Adapting to the novel environment related to the initiation or further dissemination of infection requires Candida fungi to respond immediately and effectively to the stress associated with the colonization of a new infectious niche, consisting of fluctuations in the availability of nutrients, limits in access to essential microelements, physicochemical changes in the surroundings, the influence of other microorganisms, and activity of host defense cells [148,149]. One of the most important factors that influences Candida cell metabolism during infection is the availability and type of carbon source, where glucose is preferred.…”
Section: Environmental Stress Response and Related Changes Inmentioning
confidence: 99%
“…However, some environments, that is, blood or vaginal secretions, have limited glucose concentrations, or alternative carbon sources are available, including lactate, acetate, ethanol, glycerol, fatty acids, amino acids, and N-acetylglucosamine [150,151]. When settling in a new niche, fungal cells must change their metabolism to adapt to the conditions in the existing environment and to face a combination of the different stresses encountered, i.e., thermal, osmotic, oxidative, and nitrosative stress, destructive impact of different substances on the cell wall, phagocytes, and antifungal drugs action [149,152,153]. In studies by Heaney et al, it was shown that different Candida species, including multidrug-resistant C. auris, displayed rather similar sensitivity to combinatory stress, including high salt concentration, alkaline, and thermal stress; however, for individual stresses, there were some important species and strain-dependent differences [154].…”
Section: Environmental Stress Response and Related Changes Inmentioning
confidence: 99%
“…Traditionally, masking of fungal antigenic ligands has been viewed as a strategy of fungal immune evasion in invasive infections (Pellon et al, 2022). However, In the process of interaction between C. albicans and macrophages, it avoids the killing effect of macrophages by blocking the recognition by macrophages, inhibiting the maturation of phagosome or neutralizing the pH of phagosome, changing the properties of macrophages and inhibiting the sterilization, lytic output or non-lytic export pathway to change its morphology or metabolic reprogramming.…”
Section: Candida Albicans Mediates Macrophages Immune Escapementioning
confidence: 99%
“…Adhesins are glycoproteins that enable yeast to adhere to epithelial and endothelial cells[ 40 ]. Invasins are specialized proteins by which C. albicans stimulates host cells towards endocytosis by binding to host cell ligands[ 41 ]. The target ligands are E-cadherin on epithelial cells and N-cadherin on endothelial cells[ 42 ].…”
Section: Candida As a Paramount Fungal Pathogenmentioning
confidence: 99%